Automatic completion of geometric models from point clouds for analyzing historic timber roof structures - Özkan, Taşkın; Pfeifer, Norbert; Hochreiner, Georg (Frontiers in Built Environment, 2024)
The utilization of laser scanners has become increasingly popular in the engineering community to collect accurate and dense 3D data on timber roof structures. Point clouds, produced either by scanning or by photogrammetry, can subsequently be processed via specialized software to create a geometric model of individual components in the roof structure manually. Manual modeling of each structural element in a computeraided design (CAD) respective structural analysis software is a labor-intensive and time-consuming process, whereas automatic modeling typically leads to incomplete results in terms of the number and the size of individual beams due to shortcomings in data acquisition or data processing. In the context of structural assessment, full-scale modeling of each beam is mandatory for a holistic analysis of the structure's health. This study fills the gap between automated roof structure models and preliminary structural assessment through a hierarchical analysis and refinement of the geometric model. The proposed method was applied to two different roof structures. The structural assessment shows that it is feasible to import and process the generated models in structural analysis software. The resulting structural models indicate that the workflow replaces months of time consumption with optional mistakes due to a personal contribution to less than a week without uncertainties by humans.